Dominant platform capability, symbiotic strategy and the construction of "Internet + WEEE collection" business ecosystem：A comparative study of two typical cases in China. (1st May 2020) - Sun, Qiao; Wang, Chang; Zhou, Yifang; Zuo, Lyushui; Tang, Jianxiong
Abstract: "Internet + waste electrical and electronic equipment (WEEE) collection" business ecosystems have attracted considerable attention from industry circles, and they are widely used in practice. However, the construction mechanism of "Internet + WEEE collection" business ecosystems has not been explored. In this paper, based on the mode of entry, "Internet + WEEE collection" platforms are divided into two types: platforms derived from an Internet company (PDICs) and platforms derived from a recycling company (PDRCs), and two typical corresponding platforms are analyzed using a double-case study to explore the interaction and mechanism between dominant platform capability, symbiotic strategy and business ecosystem construction. The results show the following: (1) different types of "Internet + WEEE collection" platforms have different dominant platform capabilities and then construct different business ecosystems based on their capabilities. PDICs take digital capability as the dominant platform capability and prefer to form an embedded business ecosystem, while PDRCs usually take network capability as the dominant platform capability and try to build a central business ecosystem. (2) PDICs and PDRCs prefer different symbiotic strategies, and the strategies affect the construction of business ecosystems. The strategy of mutualism symbiosis is adopted by PDICs, and it promotes them to build an embedded business ecosystem. PDRCs prefer the strategy of predation symbiosis, and they choose to construct a central business ecosystem. (3) Dominant platform capability can also affect the construction of business ecosystems through the symbiotic strategy. This study contributes to revealing the internal logic of "Internet + WEEE collection" business ecosystems construction in theory and helps platforms achieve sustainable development in practice.